Higher initial planting densities for South African-grown Pinus patula sawlog trees: the effect on stem form and land expectation value - Charlton, Ryan A. (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScFor)--Stellenbosch University, 2018.